The Cedar Project WelTel mHealth intervention for HIV prevention in young Indigenous people who use illicit drugs: study protocol for a randomized controlled trial. Issue 1 (December 2016) - Jongbloed, Kate; Friedman, Anton; Pearce, Margo; Van Der Kop, Mia; Thomas, Vicky; Demerais, Lou; Pooyak, Sherri; Schechter, Martin; Lester, Richard; Spittal, Patricia
Abstract Background Despite successes in preventing and treating HIV, Indigenous people in Canada continue to face disproportionately high rates of HIV infection. Programs that support healing from lifetime trauma, support connection to culture, and reduce drug-related harms are critical to preventing HIV among young Indigenous people who use drugs. The Cedar Project WelTel mHealth intervention proposed here is a structured mobile-phone initiative to connect young Indigenous people who use drugs with Cedar Case Managers in a community-based setting. The intervention consists of a package of supports, including a mobile phone and cellular plan, weekly two-way text messaging, and support from Cedar Case Managers. Methods The Cedar Project WelTel mHealth study is a multi-site Zelen pre-randomized trial to measure the effect of a two-way supportive text-message intervention to reduce HIV vulnerability among young Indigenous people who use illicit drugs in two Canadian cities. The trial is nested within the Cedar Project, an ongoing cohort study addressing HIV and hepatitis C vulnerability among young Indigenous people who use drugs in Vancouver and Prince George, British Columbia. The Cedar Project Partnership, an independent body of Indigenous Elders, leaders, and health/social service experts, governs all aspects of the study. Two hundred participants will be followed over a 16-month period, with HIV propensity score at 6 months as the primary outcome. Secondary outcomes include HIV propensity at 1 year, HIV risk, resilience, psychological distress, access to drug-related services, and connection to culture measured at 6 months and 1 year. Primary analysis is by intention to treat. Discussion Culturally safe interventions that address barriers to HIV prevention while supporting the strength of young Indigenous people who use drugs are urgently needed. Despite presenting a tremendous opportunity to connect young, highly transient Indigenous people who use drugs to prevention services, supportive two-way mHealth programs have yet to be tested for HIV prevention in a community-based setting with this population. Trial registration ClinicalTrials.gov NCT02437123https://clinicaltrials.gov/show/NCT02437123 (registered 4 May 2015). Protocol version: 24 July 2015.